Deregulated matriptase activity in oral squamous cell carcinoma promotes the infiltration of cancer‐associated fibroblasts by paracrine activation of protease‐activated receptor 2. Issue 1 (23rd September 2016) - Kanemaru, Ai; Yamamoto, Koji; Kawaguchi, Makiko; Fukushima, Tsuyoshi; Lin, Chen‐Yong; Johnson, Michael D.; Camerer, Eric; Kataoka, Hiroaki
Abstract : Cancer‐associated fibroblasts (CAFs) are known to contribute to cancer progression. We have reported that cell surface expression of hepatocyte growth factor activator inhibitor 1 (HAI‐1) is decreased in invasive oral squamous cell carcinoma (OSCC) cells. This study examined if HAI‐1‐insufficiency contributes to CAF recruitment in OSCC. Serum‐free conditioned medium (SFCM) from a human OSCC line (SAS) stimulated the migration of 3 human fibroblast cell lines, NB1RGB, MRC5 and KD. SFCM from HAI‐1‐knockdown SAS showed an additive effect on the migration of NB1RGB and MRC5, but not KD. SAS SFCM induced protease‐activated receptor‐2 (PAR‐2) expression in NB1RGB and MRC5, but not in KD, and a PAR‐2 antagonist blocked the stimulatory effect of HAI‐1 knockdown on migration of the PAR‐2 expressing cell lines. Moreover, HAI‐1‐deficient SFCM showed additive stimulatory effects on the migration of wild‐type but not PAR‐2‐deficient mouse fibroblasts. Therefore, the enhanced migration induced by HAI‐1‐insufficiency was mediated by PAR‐2 activation in fibroblasts. This activation resulted from the deregulation of the activity of matriptase, a PAR‐2 agonist protease. HAI‐1 may thus prevent CAF recruitment to OSCC by controlling matriptase activity. When HAI‐1 expression is reduced on OSCC, matriptase may contribute to CAF accumulation by paracrine activation of fibroblast PAR‐2. Immunohistochemical analysis of resected OSCC revealed increased PAR2‐positive CAFs in 35% (33/95) of the cases studied. The increased PAR‐2 positive CAFs tended to correlate with infiltrative histology of the invasion front and shorter disease‐free survival of the patients. Abstract : What's new? Cancer‐associated fibroblasts (CAFs) contribute to cancer progression, with many factors already known to promote their recruitment. Using oral squamous cell carcinoma (OSCC) as a model, this study shows for the first time that deregulated pericellular matriptase activity also contributes to the recruitment of CAFs by paracrine activation of fibroblast PAR‐2. Insufficient HAI‐1 in OSCC cells resulted in increased extracellular matriptase activity and activated PAR‐2 expressed on fibroblasts, leading to their enhanced migration. Immunohistochemical analysis of resected OSCC tissues revealed that 35% of cases showed PAR‐2 immunoreactivity in CAFs, which tended to correlate with more invasive histology and shorter disease‐free survival.